The Development of Student Worksheet Based on Contextual Approach about Protist for Senior High School Grade X - Putri Dharmayanti; Zulyusri Zulyusri; Siska Aulia Farma; Ristiono Ristiono (Universitas Negeri Padang, 2019)
The purpose of this research is to develop student worksheet based on Contextual Approach about Protist for SMA/MA. This research includes development research with reference to 4-D model. The experimental subject in this research is the subject of expert, namely two lecturers of Biology in State University of Padang and science teacher of National Junior High School of Sumpur, as well as the subject of grade X students of Sumpur SMA/MA as potential users of the product. Data in this research is primary data. Instrument collecting data used is validity sheet and sheet of practicality sheet by teacher and student. Result of validity is 86,2% with criteria is valid, result of practicality test is 87,5% by teacher with practical criteria and practice test by learner equal to 88% with practical criteria.